Clinical Decision Making and Mental Health: On Challenges in Assessment, Junk Science and Social Trends - Mandić, David (Psihološka istraživanja, 2025)
Judgement and decision making are rife with cognitive biases. Despite their everyday fitness, these can affect clinical assessment, which may lead to erroneous decisions. All specialists are prone to bias; these vulnerabilities permeate social strata, while people underestimate their own proneness to these errors. In mental health, statistical prediction and empirically robust tests should compensate for such errors. Therefore, the paper reviews basic heuristics and associated biases in practice, namely, representativeness, availability, and anchoring. Furthermore, it is elaborated how clinical decision making is influenced by social factors, thus giving rise to groupthink. Experience without adequate training might even worsen decision making by overconfidence. Psychoeducation on biases, among others, shows promise in countering them. In addition, examples that demonstrate in which way heuristics and biases contribute to the receptiveness to popular psychology, myths, pseudoscience, misinformation, alternative health methods and radicalization, are provided in the paper. Relativization of evidence and disinformation present crucial challenges to the acceptance of science and to the democratic society. Science communication should influence market offering and consult social psychological communication research in combatting disinformation, useful for both undergraduates and the lay audience.